Pelaksanaan Pembelajaran Motorik Kasar di PAUD sekolahalam Minangkabau Padang - Oksimiliya Wirda; Indra Yeni; Rakimahwati Rakimahwati (SELING: Jurnal Program Studi PGRA, 2020)
This study aims to describe the application of gross motor learning in PAUD sekolahalam minangkabau Padang. The type of research used is a qualitative method. in research informan is class facilitators, outbound facilitators, and school principals. Data collection techniques used consisted of observation, interviews, and documentation. Data analysis techniques are carried out through data collection, data reduction, and drawing conclusions. While the data validation technique uses triangulation techniques. Research conducted at PAUD sekolahalam minangkabau Padang shows that the implementation is carried out through planning which consists of yearly plans, weekly plans, and daily plans. The implementation was carried out with various activities such as outbound, gardening, and outing through several methods such as hands-on training, role playing, and field trips. The assessment is carried out by the facilitator when learning takes place, while the evaluation is carried out at the end of the learning activity by the facilitator.